Creative Quickies, Vol. II Allan Jones and Janifer Gorney. - Jones, Allan (Distributed by ERIC Clearinghouse, 1981)
Activities intended to encourage creative expression in all areas of the K-6 curriculum are presented for use by parents and teachers. Language and visual arts activities are emphasized and are integrated with the areas of social science, mathematics, science, self-esteem, and values clarification. The amount of materials needed and the preparation time are meant to be minimal. Activities are organized into four sections. The first section provides 31 activities dealing exclusively with the use of magazines. The second section contains 35 creative writing and quick art ideas. Twenty-one learning dittos that have been "turn-on's" for children are provided in the third section. Eleven interesting shapes with ideas for stories and art printed on the back of each are presented in the fourth section of this guide. (JW)